2017
DOI: 10.1038/ngeo2985
|View full text |Cite
|
Sign up to set email alerts
|

National baselines for the Sustainable Development Goals assessed in the SDG Index and Dashboards

Abstract: The Sustainable Development Goals (SDGs) -agreed in 2015 by all 193 member states of the United Nations and complemented by commitments made in the Paris Agreement -map out a broad spectrum of economic, social and environmental objectives to be achieved by 2030. Reaching these goals will require deep transformations in every country, as well as major efforts in monitoring and measuring progress. Here we introduce the SDG Index and Dashboards as analytical tools for assessing countries' baselines for the SDGs t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
220
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 423 publications
(262 citation statements)
references
References 25 publications
2
220
0
4
Order By: Relevance
“…Weighting impacts of the outcome of the composite indicator as well as ranking of country performance therefore requires important considerations. This paper applies equal weighting similar to other research that has constructed SGD indices and indicators, particularly the work of the SDSN [26,27]. These prior analyses justified equal weighting for its reflection of the commitment by policy makers to treat all SDGs equally important.…”
Section: Normalization and Weighting Of Indicatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Weighting impacts of the outcome of the composite indicator as well as ranking of country performance therefore requires important considerations. This paper applies equal weighting similar to other research that has constructed SGD indices and indicators, particularly the work of the SDSN [26,27]. These prior analyses justified equal weighting for its reflection of the commitment by policy makers to treat all SDGs equally important.…”
Section: Normalization and Weighting Of Indicatorsmentioning
confidence: 99%
“…However, given time limitations, for the current paper this could not be done. Nevertheless, given that most SDG indicators and dashboards are based on equal weights as indicated above [17,27], the current analysis could spur discussions and improvements of monitoring and measuring of progress in the agriculture SDGs. Combining this assessment with the progress reviews of regional and continental commitments in the agriculture sector provide useful information that could be used to engage different stakeholders in promoting investments in different sub-sectors of agriculture to enhance performance and contribution towards achievements of inclusive and sustainable growth.…”
Section: Robustness and Sensitivity Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…This assessment indicated that the 149 countries for which adequate data were available face fundamental challenges in achieving the SDGs. Both Index and Dashboards will be updated every year for monitoring progress (Schmidt‐Traub et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies using increments of global mean temperature increase vary in their choice of baseline [5]. Most of the studies assessing climate change impacts in Europe focus at fixed time periods, for example, mid-or end century [6,7].…”
Section: Introductionmentioning
confidence: 99%